Cost-effectiveness analysis of radiofrequency renal denervation for uncontrolled hypertension in Sweden - T. Kahan; M. L. Johansen; A. M. Ryschon; K. N. Cao; M. D. Kolovetsios; P. Lindgren; J. B. Pietzsch (Blood Pressure)
Introduction Radiofrequency renal denervation (RF RDN) is a catheter-based therapy for uncontrolled hypertension. This model-based analysis examined the cost-effectiveness of RF RDN in Sweden.Methods Clinical events, costs, quality-adjusted life-years (QALYs) were projected over 10-year and lifetime horizons using a decision-analytic Markov model. Primary health states, included hypertension alone, myocardial infarction (MI), stroke, other symptomatic coronary heart disease (CHD), heart failure (HF), end-stage renal disease (ESRD), and death. Health state transitions were informed by multivariate risk equations. Clinical evidence from the SPYRAL HTN-ON MED trial informed the treatment effect modelled (–4.9 mmHg reduction in office systolic blood pressure (SBP) vs. sham). The base case was conducted from the Swedish healthcare payer perspective. The primary outcome was the incremental cost-effectiveness ratio (ICER),RF RDN vs. standard of care (SoC), evaluated against an assumed willingness-to-pay threshold of SEK 500,000 per QALY gained. Extensive sensitivity analyses were performed.Results At 10-years, the relative risks with RF RDN were 0.80 for stroke, 0.88 for MI, 0.89 for CHD, 0.72 for HF, 0.96 for ESRD, 0.86 for cardiovascular death and 0.93 for all-cause death. Over lifetime, RF RDN led to incremental costs of SEK 63,136 (total costs SEK 497,498 vs. SEK 434,362) and incremental QALY gain of 0.45 (14.79 vs. 14.34), yielding an ICER of SEK 139,280 per QALY gained. RF RDN was cost-effective across all scenarios and sensitivity analyses.Conclusion Model projections suggest RF RDN to be a cost-effective therapy for uncontrolled including resistant hypertension in Sweden based on contemporary clinical evidence.